Art is-- the permanent revolution [videorecording (DVD)] : prints and protest - Schneer, Deborah; Kirchheimer, Manfred; Kirchheimer, Manfred; Kirchheimer, Manfred; Kirchheimer, Manfred; Abeles, Sigmund, 1934-; Chernow, Ann, 1936-; Marcus, Paul; Reed, James (First Run Features, 2012)
"The anger and outrage captured by graphic artists have defined revolutions through the centuries. Printmakers have depicted the human condition in all its glories and struggles so powerfully that perceptions, attitudes and politics have been dramatically influenced ... three contemporary artists and a master printer explore how social reality and protest are conveyed in art"--Container.